A novel protocol to reduce bleeding associated with alteplase treatment of HVAD pump thrombosis. Issue 2 (February 2022) - Lewis, Tyler C; Emmarco, Amy; Gidea, Claudia G; Reyentovich, Alex; Smith, Deane E; Moazami, Nader
Pump thrombosis remains a feared complication for patients implanted with durable left ventricular assist devices. Optimal treatment is unknown, but consists of either pharmacologic fibrinolysis or surgical pump exchange. Fibrinolysis is less invasive, but carries a significant risk of intracerebral hemorrhage. We present four cases of LVAD pump thrombosis successfully treated with a novel protocol that consists of low-dose four-factor prothrombin complex concentrate to reverse baseline INR elevation prior to alteplase administration to minimize the risk for intracerebral hemorrhage.